Job perceptions following statewide evidence-based treatment implementation. Issue 4 (19th December 2016) - Green, Amy E.; Cafri, Guy; Aarons, Gregory
Abstract : Purpose: The concerns that implementing a new structured innovation with increased oversight may lead to reduced job autonomy and poorer work attitudes. These concerns have been cited as a barrier to evidence-based treatment (EBT) implementation. However, previous research found lower turnover among child welfare providers implementing an EBT with fidelity monitoring compared to those administering services as usual (SAU). The authors hypothesized that changes in job autonomy, job satisfaction, and organizational commitment would be no worse among providers in EBT conditions and fidelity monitoring conditions compared to SAU and no monitoring conditions. Design/methodology/approach: Survey data were collected from 208 service providers over four waves at six month intervals as part of a 2 (EBT vs SAU) by 2 (fidelity monitoring vs no monitoring) hybrid effectiveness-implementation trial. Superiority testing was conducted to determine whether there were significant differences over time on the outcomes as a function of experimental condition. Non-inferiority testing examined whether the EBT condition is not inferior to SAU and monitoring not inferior to no monitoring on the outcomes. Findings: No evidence of superiority was found for any conditions over time on the outcomes. Non-inferiority testing indicates EBT is not inferior to SAU and monitoring is not inferior to no monitoring on the outcomes. Originality/value: This study provide empirical quantitative data regarding job attitudes and job autonomy perceptions over time following EBT implementation. In light of the current findings, concerns regarding the impact of EBT implementation on provider job perceptions should be minimized.